Exploration of chest wall perforator vascular anatomy on standard breast MRI: A potential aid to chest wall perforator flap planning. Issue 5 (May 2022) - Heeney, A.; Bhaludin, B.; St John, E.R.; O'Connell, R.; Krupa, K.; Rusby, J.E.; Allen, S.; Barry, P.A.
Summary: Local chest wall perforator flaps (CWPFs) are a volume replacement technique permitting breast-conserving surgery in patients who otherwise may require a mastectomy. These flaps are based on one or more perforating arteries arising from the lateral chest wall that travel through the soft tissue and into the sub-dermal plexus to perfuse the flap. Examples include the lateral intercostal and lateral thoracic artery perforators (LICAP and LTAP, respectively). Cross-sectional imaging of perforating vessels is not routinely performed, and vessels are mapped pre- and peri-operatively using a hand-held acoustic doppler device. As many breast cancer patients undergo pre-operative MRI scanning for oncological purposes, we investigated the role of MRI in mapping the vascular anatomy to aid with the surgical planning of CWPFs. We collated data retrospectively on a cohort of breast cancer patients who underwent breast MRI as part of routine pre-operative imaging. Axial 3D high-resolution dynamic contrast-enhanced MRI sequences with multiplanar reconstructions were analysed by a consultant radiologist. The presence and calibre of lateral chest wall perforator vessels were assessed. Fifty patients were suitable for inclusion. A consistent pattern of lateral chest wall vasculature was observed. Forty-eight patients (96%) demonstrated a bilateral lateral thoracic artery (LTA) descending inferiorly along the chest wall with two-thirds of these communicating with perforating intercostal vessels. True independent LICAP vessels were identified in six patients. From our observations, lateral CWPFs are dependent on an intricate intercommunication between intercostal vessels and the LTA which in turn supply perforators to the lateral chest wall donor site.